The Laghusiddhāntakaumudī of Varadarāja : a primer of Pāṇini's grammar. Vol. 1 - Varadarāja; Kanshi Ram; Caturvedī, Mithileśa (Delhi : Motilal Banarasidass Publishers, 2010)
Abridgment of Siddhāntakaumudī by Bhaṭṭojī Dīkṣita, classical commentary on Aṣṭādhyāyī of Pāṇini, work on Sanskrit grammar.
Prijevod djela: Laghusiddhāntakaumudī.
Bibliografija: str. 585-588 i kazala.
Keywords: sanskrt -- gramatika; Bhaṭṭojī Dīkṣita -- Siddhāntakaumudī; Pāṇini -- Aṣṭādhyāyī -- komentari